Capacidad antimicrobiana del hidróxido de calcio y metronidazol, ciprofloxacina, minociclina (componentes de la pasta triantibiotica) frente a staphylococcus aureus, revisión de la literatura (2020)
Persistent bacteria within the dentin tubules are the most common reason for recurrence of apical periodontitis. Calcium hydroxide has been widely used as an endodontic drug, its antibacterial action is based on its ability to maintain a high pH in the root canal. A mixture of metronidazole, ciprofloxacin, and minocycline, known as triantibiotic paste, has been used as an intracanal drug to disinfect the root canal during tissue regeneration. OBJECTIVE: To determine the antimicrobial capacity of calcium hydroxide and metronidazole, ciprofloxacin, minocycline (components of the triantibiotic paste) against Staphylococcus aureus through a literature review. METHODOLOGY: The sample was selected based on the review of 30 articles, using 5 databases for this research from February 2019 to September 2020 in a publication interval from 1990 to 2020 of indexed journals. RESULTS: It was found that calcium hydroxide presented an inhibitory effect which was considered optimal at 24 hours, observing certain bacterial growth of S. aureus. The behavior of ciprofloxacin, metronidazole, minocycline against S. aureus was observed individually, giving as a deduction the resistance of S. aureus, especially to ciprofloxacin and metronidazole, minocycline also presented a high degree of sensitivity to S. aureus. CONCLUSION: Staphylococcus aureus was found to be more susceptible to the bactericidal action of calcium hydroxide preparations. The use of minocycline may provide a more suitable effect against S. aureas. KEY WORDS: Sthaphylococcus aureus, calcium hydroxide, triantibiotic paste, minocycline, metronidazole, ciprofloxacin.